2010
DOI: 10.1021/la103875w
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting Aggregates in Mixed Aerosol OT and Cholesterol Microemulsions

Abstract: Dynamic light scattering and NMR spectroscopic experimental evidence suggest the coexistence of two compositionally different self-assembled particles in solution. The self-assembled particles form in solutions containing water, Aerosol OT (AOT, sodium bis(2-ethylhexyl) sulfosuccinate) surfactant, and cholesterol in cyclohexane. In a similar series of studies carried out in 1-octanol only one aggregate type, that is, reverse micelles, is observed. Dynamic light scattering measurements reveal the presence of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 75 publications
1
25
0
Order By: Relevance
“…5 are characteristic for cholesterol [66], and randomly shaped structures are likely cholesterol and surfactant aggregates. Aggregates of cholesterol have previously been reported to form in AOT solutions with cholesterol in isooctane [67]. Summarizing, we have documented gel-phase formation in the 3 : 1 mixture of AOT and lecithin surfactant blend.…”
Section: Probing the Interaction Of Carboplatin With Dppc And Cholestsupporting
confidence: 68%
“…5 are characteristic for cholesterol [66], and randomly shaped structures are likely cholesterol and surfactant aggregates. Aggregates of cholesterol have previously been reported to form in AOT solutions with cholesterol in isooctane [67]. Summarizing, we have documented gel-phase formation in the 3 : 1 mixture of AOT and lecithin surfactant blend.…”
Section: Probing the Interaction Of Carboplatin With Dppc And Cholestsupporting
confidence: 68%
“…90 All samples used in further studies were transparent, and formation of RMs was confirmed by using dynamic light scattering (Wyatt DynaPro Titan) and conductivity measurements as described previously 90. 93…”
Section: Methodsmentioning
confidence: 99%
“…[48,90] All samples used in further studies were transparent, and formation of RMs was confirmed by using dynamic light scattering (Wyatt Dy-naPro Titan) and conductivity measurements as described previously. [90,93] Sample preparation for EPR spectroscopy: Solutions of the 1:2 complex, [VO(dipic) 2 ] 2À , were prepared from aqueous solutions of VOSO 4 (2, 4, and 10 mm) and solid Na 2 dipic with a 25-fold molar ligand-to-metal ratio. The solution pH was adjusted to 7.3 AE 0.4 with small aliquots of NaOH and HCl.…”
Section: Methodsmentioning
confidence: 99%
“…[61] Cuvettes were washed with ethanol, then with doubly distilled water, and then dried with acetone. The cleanliness of the cuvettes used for measurements was of crucial importance for obtaining reliable and reproducible data.…”
Section: Generalmentioning
confidence: 99%